Neuroticism and Close Relationships: How Negative Affect is Linked with Relationship Disaffection in Couples. Issue 2 (15th March 2018) - Saeed Abbasi, Irum; Rattan, Neelam; Kousar, Tehmina; Khalifa Elsayed, Fatma
Abstract: Dispositional vulnerability afforded by personality can lead to adverse relationship outcomes. Neuroticism personality is bundled with a disadvantageous temperament that makes people high in neuroticism more sensitive to negativity. Consequently, neuroticism signifies negative emotions such as anger, anxiety, and sadness. Neuroticism is also inversely related to marital satisfaction. The present study examined the relationship between relationship disaffection (emotional indifference) and negative affect in the context of neuroticism. The present study included 819 participants (511 females, 308 males) between the ages of 18 years to 74 years ( M = 27.16, SD = 10.58) who were in a committed or married heterosexual relationship. Our mediation model explored the relationship between neuroticism and relationship disaffection with negative affect acting as a mediator. We found a modest indirect relationship between neuroticism and relationship disaffection via negative affect. Acknowledging that individuals high in neuroticism are temperamentally sensitive to negative stimuli, therapists can assist partners in learning ways to curb negative mood to combat relationship disaffection. Future studies can build on these findings and design research addressing the limitation of the present study.